2019
DOI: 10.1017/jfm.2019.446
|View full text |Cite
|
Sign up to set email alerts
|

Convective heat transfer along ratchet surfaces in vertical natural convection

Abstract: We report on a combined experimental and numerical study of convective heat transfer along ratchet surfaces in vertical natural convection (VC). Due to the asymmetry of the convection system caused by the asymmetric ratchet-like wall roughness, two distinct states exist, with markedly different orientations of the large-scale circulation roll (LSCR) and different heat transport efficiencies. Statistical analysis shows that the heat transport efficiency depends on the strength of the LSCR. When a large-scale wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…where Prandtel number (Pr = ) is assumed to be Pr = 1 for dry air. Therefore one partial elliptical differential Equation (7)…”
Section: Temperature Field Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…where Prandtel number (Pr = ) is assumed to be Pr = 1 for dry air. Therefore one partial elliptical differential Equation (7)…”
Section: Temperature Field Formulationmentioning
confidence: 99%
“…Experimental studies along with numerical estimations of ventilation room have been performed by [10], [21] and [23]. The cases of 3D cavity with heat source have been performed by [4,7]. Finally, more information about CFD numerical discussion can be found in [12,19,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is recognised widely that the mean velocity profile in wall shear flows cannot be applied to describe vertical convection (VC), due to the effect of buoyancy (Ke et al 2020). The VC is the buoyancy-driven flow along a vertical heated wall, and it usually includes three configurations (Hölling & Herwig 2005;Howland et al 2022): (a) a single heated vertical plate immersed in an ambient fluid (Tsuji & Nagano 1988a,b;Wells & Worster 2008;Ke et al 2020), abbreviated as 'plate VC' hereafter; (b) a closed cavity with two opposite sidewalls heated at different temperatures (Shishkina 2016;Jiang et al 2019;Wang et al 2021;Zwirner et al 2022), abbreviated as 'cavity VC' hereafter; (c) a vertical infinite channel with periodic boundary conditions in the wall-parallel directions (Pallares et al 2010;Ng et al 2013Ng et al , 2015Howland et al 2022;Ching 2023), abbreviated as 'channel VC' hereafter. This study focuses on the last configuration of VC, as shown in figure 1(a).…”
Section: Introductionmentioning
confidence: 99%
“…Further work has examined the modifications created by ratchet surfaces (Jiang et al. 2019). All these studies typically involved bounding surfaces kept at prescribed uniform temperatures.…”
Section: Introductionmentioning
confidence: 99%